2020
DOI: 10.1097/bpb.0000000000000807
|View full text |Cite
|
Sign up to set email alerts
|

Hip morphology in slipped capital femoral epiphysis

Abstract: Several mechanical factors have been related to slipped capital femoral epiphysis (SCFE). Main aim of this study is to investigate the acetabular coverage and acetabular version in unilateral SCFE hips in order to detect a potential pincer-type deformity as predisposing factor; second, we compared those measurements either to the contralateral, uninvolved hips either to a matched healthy control population. A total of 85 patients treated for unilateral SCFE were retrospectively reviewed. The lateral center-edg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Sankar et al 11 found a relationship between acetabular retroversion and SUFE using the radiological COS and PWS, with more recent studies showing an increased incidence of the same signs when compared to a matched control population. 38 …”
Section: Discussionmentioning
confidence: 99%
“…Sankar et al 11 found a relationship between acetabular retroversion and SUFE using the radiological COS and PWS, with more recent studies showing an increased incidence of the same signs when compared to a matched control population. 38 …”
Section: Discussionmentioning
confidence: 99%
“…Slipped Capital Femoral Epiphysis (SCFE) is a pathology developing during the pubertal growth spurt [3] presenting with a broad spectrum of severity [1]. Accordingly treatment has to be individualized [2]. The goal of treatment is to prevent secondary coxarthrosis, which in mild slips is best achieved by in-situ pinning to prevent further increase of displacement [19], combination with Imhäuser-Southwick intertrochanteric osteotomy on more severe slips [4], or direct reduction of the slipped epiphysis to restore anatomy as first described by DUNN [1].…”
Section: Introductionmentioning
confidence: 99%